Kajian Terhadap Dinamika Universitas Al-Azhar dan Pembaharuan Pendidikan di Mesir, Serta Pengaruhnya pada Dunia Islam - Tini Melinda Nst; Muhammad Zalnur; Fauza Mahyudi (JOURNAL SAINS STUDENT RESEARCH, 2024)
Al-Azhar University is evidence of the oldest Islamic education in the world, founded during the Fatimid dynasty in Egypt and functioned as a center of Islamic studies and a center for the spread of Ismaili Shi'a teachings. Over time and the change of Islamic government, al-Azhar mosque turned into a madrasa to spread sunni Islam and has now become a university that gave birth to many scholars who gave birth to new views and ideas of reform so as to influence the development of education and the Islamic world throughout the world. This research aims to find out the dynamics of universities and educational reforms in Egypt that have an impact on Muslims globally. This research uses library research with references from books, articles and historical analysis of Al-Azhar. The result of this research is the knowledge of al-Azhar from the Fatimid dynasty to educational reform in Egypt.